Exploring the Impact of Trauma History on the Mental Health Presentations of Youth who have Experienced Commercial Sexual Exploitation and Trafficking. Issue 4 (2nd October 2022) - Self-Brown, Shannon R.; Osborne, Melissa C.; Lee, NaeHyung; Perry, Elizabeth W.; Kinnish, Kelly
Abstract: This study explores the types and extent of potentially traumatic events that youth who have experienced commercial sexual exploitation and trafficking (CSE/T) report, and how these experiences influence mental health. CSE/T youth (N = 110, 11–19 years old) referred to Trauma-Focused Cognitive Behavioral therapists affiliated with Project Intersect provided self-report data between August 2013 and March 2020 at the start (baseline), mid-point, and completion of therapeutic services. This study focuses on the baseline data collected. Bivariate relationships were analyzed, and where bivariate associations were statistically significant, associations were assessed in adjusted regression models. Two logistic regressions were performed: one for the adjusted associations between types of potentially traumatic events reported by CSE/T youth and the outcome PTSD, and a second for the outcome emotional distress. Results indicated that polytrauma was significantly associated with PTSD diagnosis among CSE/T youth. Direct violence victimization and polytrauma were significantly associated with CSE/T youth emotional distress. Results inform behavioral medicine practitioner considerations for how to appropriately assess the potentially traumatic experiences of CSE/T youth, and how these experiences may differentially impact the mental health presentations of youth in clinical treatment. Effective treatment may include precision-based customization of evidence-based practices to ensure that the diverse traumatic experiences and related symptomatology of CSE/T youth are effectively addressed.